Review on Gas-to-Liquids Conversion Technology: Lessons from Case Studies and Potential Strategies for Implementation in Tanzania - Kihedu, Joseph H.; Mziray, William E. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This review paper explores the transformative potential of Gas-to- Liquids (GTL) technology for harnessing Tanzania's vast natural gas resources. With significant discoveries of natural gas reserves totalling up to 57 Tcf in fields such as Songosongo, Mnazi Bay, Block 1, 2, 3 and 4. Tanzania is positioned to leverage GTL technology to convert these resources into high-value liquid fuels like gasoline, diesel and naphtha. Review of GTL process, its products and applications has been done. By analysing successful GTL projects globally and drawing lessons applicable to Tanzania, this paper provides strategic recommendations for policymakers and stakeholders to foster GTL development. It further addresses the potential considerations that Tanzania may be required to attain with GTL implementation, including capital projections, technological complexities, and the need for supportive policy frameworks. GTL technology does not only promise to enhance energy security and reduce dependency on imported fuels but also offers substantial economic benefits through job creation, infrastructure development and increase export revenues. Adoption of GTL technology in Tanzania could play a pivotal role in diversifying the energy mix, enhancing economic growth and promoting sustainable development